TRADITIONAL KNOWLEDGE OF MEDICINAL PLANTS IN THE SERRA DE MARIOLA NATURAL PARK, SOUTH-EASTERN SPAIN - Belda, A; ZaragozÃ, B; Belda, I; MartÃnez, J E; Seva, E (African Journal of Traditional, Complementary and Alternative Medicines, 2012)
The present study aims to inventory and analyse the ethnobotanical knowledge about medicinal plants in the Serra de Mariola Natural Park. In respect to traditional uses, 93 species reported by local informants were therapeutic, 27 food, 4 natural dyes and 13 handcrafts. We developed a methodology that allowed the location of individuals or vegetation communities with a specific popular use. We prepared a geographic information system (GIS) that included gender, family, scientific nomenclature and common names in Spanish and Catalan for each species. We also made a classification of 39 medicinal uses from ATC (Anatomical, Therapeutic, Chemical classification system). Labiatae (n=19), Compositae (n=9) and Leguminosae (n=6) were the families most represented among the plants used to different purposes in humans. Species with the most elevated cultural importance index (CI) values were Thymus vulgaris (CI=1.431), Rosmarinus officinalis (CI=1.415), Eryngium campestre (CI=1.325), Verbascum sinuatum (CI=1.106) and Sideritis angustifolia (CI=1.041). Thus, the collected plants with more therapeutic uses were: Lippia triphylla (12), Thymus vulgaris and Allium roseum (9) and Erygium campestre (8). The most repeated ATC uses were: G04 (urological use), D03 (treatment of wounds and ulcers) and R02 (throat diseases). These results were in a geographic map where each point represented an individual of any species. A database was created with the corresponding therapeutic uses. This application is useful for the identification of individuals and the selection of species for specific medicinal properties. In the end, knowledge of these useful plants may be interesting to revive the local economy and in some cases promote their cultivation.